Correlations among Psychological Resilience, Self-Efficacy, and Negative Emotion in Acute Myocardial Infarction Patients after Percutaneous Coronary Intervention - Liu, Neng; Liu, Shaohui; Yu, Nan; Peng, Yunhua; Wen, Yumei; Tang, Jie; Kong, Lingyu (Frontiers in Psychiatry, 2018)
Objective: We investigated the influencing factors of the psychological resilience and self-efficacy of acute myocardial infarction (AMI) patients after percutaneous coronary intervention (PCI) and the relationships of psychological resilience and self-efficacy with negative emotion. Methods: Eighty-eight participants were enrolled. Psychological resilience, self-efficacy, and negative emotion were assessed with the Psychological Resilience Scale, Self-Efficacy Scale, Zung Self-Rating Anxiety Scale (SAS), and Zung Self-Rating Depression Scale (SDS), respectively. Furthermore, the relationships of psychological resilience and self-efficacy with negative emotion were investigated. Results: The average scores of psychological resilience, self-efficacy, anxiety, and depression were 70.08 ± 13.26, 21.56 ± 9.66, 53.68 ± 13.10, and 56.12 ± 12.37, respectively. The incidences of anxiety and depression were 23.90% (21/88) and 28.40% (25/88), respectively. The psychological resilience and self-efficacy scores of AMI patients after PCI varied significantly with age and economic status. SAS scores and SDS scores were significantly negatively correlated with psychological resilience and self-efficacy. Conclusions: Negative emotions in AMI patients after PCI are closely related to psychological resilience and self-efficacy. Therefore, anxiety and depression could be alleviated by improving the psychological resilience and self-efficacy of patients undergoing PCI, thus improving patients’ quality of life.